Digital Management of Micro, Small and Medium Enterprises (MSME) Activities Based on the Unified Approach - Astri, Renita; Faradika, Faradika; A, M. Razi; Kamal, Ahmad (Scientific Journal of Informatics, 2021)
Purpose: Micro, Small, and Medium Enterprises (MSME) is an important part of today's Indonesian economy. The times have allowed many people to do their own business. Along with the many existing businesses, many business actors are marketing for the sustainability of their business. A web-based information system that can accommodate information about Micro, Small, and Medium Enterprises management is one of the main needs for MSME actors themselves. Methods/Study design/approach: In addition, the public can use this web-based information system to obtain detailed information on MSME and MSME products through the web. Making the web using the PHP programming language where the approach taken in the design is the Unified Approach used as a method in object-based system development. Result/Findings: From the final results of this study, it can be concluded that the web-based MSME Activity Management Information System can help mass marketing of MSME players and help related agencies to find out the development of existing MSME. Novelty/Originality/Value: The website was built can help and accelerate the marketing process for existing MSMEs and can be used as a medium of communication between MSMEs and visitors.